Towards a Moderate Indonesian Society: Strengthening and Challenging Religious Moderation - Diyana Yasmin (Jurnal Indonesia Studi Moderasi Beragama, 2024)
The practice of religious values and teachings should ideally be carried out not only to fulfill the interests of its adherents but can have positive implications for adherents of other religions, in the framework of building strong social ties in the context of national life. This research aims to find out the values of religious moderation contained in it and the opportunities and challenges in welcoming the current era of modernity. The research method uses a literature study. The research data comes from research results that have been conducted and published in national online journals. The analysis method used is content analysis. The results showed that there are 9 values of religious moderation in Islam including (1) tawassuth; (2) I'tidal; (3) Tasamuh; (4); Shura; (5) Ishlah; (6) Qudwah; (7) Muwathanah; (8), Al-La'unf; (9) I'tibar Al-Urf. The results showed that Islam obliges its people to always maintain security and promote the prosperity of their country, not to destroy it. The contribution of this research is as novelty and scientific information regarding the strengthening and challenges of religious moderation in Indonesia: Toward a Moderate Society.